2. Найдите значение выражения (a-3)(b – 3) - (a + 2)(b + 2) при а+ b = -3. А) 12
В) 20
C) 16
D) 18
скажите побыстрей​

Gdvbfc Gdvbfc    1   23.08.2020 00:22    0

Ответы
VikusPadididi VikusPadididi  15.10.2020 16:09

Объяснение:

(a-3)·(b-3)  - (a+2)·(b+2) = ab - 3b - 3a + 9 - (ab + 2b + 2a + 4) =

=  ab - 3b - 3a + 9 - ab -2b - 2a - 4  =   - 3b - 3a + 9  -2b - 2a - 4 =

= - 5b - 5a + 5 = -5(a+b) + 5 = -5·(-3) + 5 = 15 + 5 = 20

Правильный ответ:

В) 20

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Физика